An introduction to autism and the autism spectrum - Volkmar, Fred (Henry Stewart Talks, 2020)
Introduction to autism, History of the development of the concept, What cause autism, How common is autism, Epidemiology of autism, Face recognition and eye tracking by individuals with autism, Brief summary of outcome and treatment (behavioral, teaching strategies, family support), Drugs and complementary and alternative treatments treatment